Using Days Alive and Out of Hospital to measure inequities and explore pathways through which inequities emerge after coronary artery bypass grafting in Aotearoa New Zealand: a secondary data analysis using a retrospective cohort - Sarah-Jane Paine; Luke Boyle; Alan Forbes Merry; Elana Curtis; Thomas Lumley; Jade Tamatea (BMJ Open)
Objectives To describe the use of days alive and out of hospital (DAOH) as a sensitive measure of equity of outcomes after surgery by comparing outcomes after a coronary artery bypass grafts (CABG) operation between Māori and non-Māori patients in Aotearoa New Zealand.Primary and secondary outcome measures We calculated unadjusted and risk-adjusted DAOH scores at three time points (30, 90 and 365 days) and compare values between Māori and non-Māori using data from the New Zealand Ministry of Health (MoH) over a 9 year period. To assess the impact of different risk factors on differences in outcome, we risk-adjust for multiple factors individually and collectively, to begin to elucidate possible pathways for equity gaps.Results After our comparisons, Māori patients experienced fewer unadjusted DAOH90 at seven out of nine deciles. After risk-adjustment, the differences ranged from 8 days to 0 days when considering different risk factors. The equity gap was widest at the lower deciles and was most reduced after adjusting for the Measuring Multi Morbidity (M3) score. The equity gap widened as the time period extended from 30 to 90 to 365 days.Conclusion Māori patients who underwent a CABG operation experienced fewer DAOH than non-Māori patients even after adjusting for multiple possible explanatory variables, and this difference increased over time postoperatively. Importantly, our results illustrate the value of DAOH as a sophisticated outcome metric that can reflect the complex and accumulative impacts of disadvantage and discrimination faced by Indigenous peoples both here in New Zealand and worldwide. It has considerable potential to increase our understanding of how and where inequities arise on the entire patient journey.